Pelatihan Sistem Informasi Geografis (GIS) Tingkat Dasar dalam Upaya Pengembangan Skill Mapping di Universitas Teuku Umar - Aminah, Siti; Maulidia, Vina; Fachruddin, Fachruddin; Aulia, Muhammad Reza; Jasmi, Jasmi (Universitas Teuku Umar, 2023)
The availability of digital data regarding geographic information has brought the changes in how we use and understand information about the earth. One of the sectors that needs to be improved and developed so that this data provision can be fulfilled is human resources, namely the ability to master mapping skills. This involves analyzing each employee's competencies in relation to specific skills, for example abilities related to specific projects, roles and tasks. The service method used is the lecture and direct demonstration method. Basic level GIS training activities for the community were held for 5 days from 16-22 March 2023, attended by 37 participants in total from various government agencies. This activity takes place in three stages, ie. the opening stage, the map making practice stage and the closing stage.